2021
DOI: 10.1108/ijsms-08-2021-0168
|View full text |Cite
|
Sign up to set email alerts
|

Gym users: an enabler in creating an acceptance of sports and fitness wearable devices in India

Abstract: PurposeThere are two-fold objectives to this research. First is to analyse the importance of technology readiness (TR) for the users in using sports and fitness wearable devices in India. And second is to explore if gymnasium (gym) users are much more technologically ready as compared to non-gym users to use sports and fitness wearable devices.Design/methodology/approachThe study uses technology readiness and acceptance model (TRAM) to examine the users' intention to use sports and fitness wearable devices. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…’s (2016) study, which the authors attribute to ease of use being mainly a firm-level acceptance construct. By contrast, Raman and Aashish (2021), Aksoy et al. (2020), Reyes-Mercado (2018) and Kim and Shin (2016) found that effort expectancy and ease of use had direct positive effects on intention to use.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…’s (2016) study, which the authors attribute to ease of use being mainly a firm-level acceptance construct. By contrast, Raman and Aashish (2021), Aksoy et al. (2020), Reyes-Mercado (2018) and Kim and Shin (2016) found that effort expectancy and ease of use had direct positive effects on intention to use.…”
Section: Discussionmentioning
confidence: 95%
“…, 2003). Raman and Aashish (2021), Aksoy et al. (2020) and Reyes-Mercado (2018) also found that performance expectancy (similar to perceived usefulness) significantly explains behavioral intention to use fitness wearables.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations